Evaluating the weight-adjusted waist index as a predictive tool for sarcopenia and mortality risk - Qingzheng Shen; Tianjing Zhou; Xiaodong Chen; Hafiz Muhammad Umar; Xinxin Yang; Xian Shen (Eating and Weight Disorders)
Abstract Purpose The weight-adjusted waist index (WWI) is a novel anthropometric measure. WWI is linked to reduced muscle mass and strength; however, its efficacy for assessing sarcopenia and predicting adverse outcomes has yet to be validated. This study compared and examined the relationship between sarcopenia and WWI across different diagnostic criteria and aimed to evaluate its potential as a predictor of sarcopenia and all-cause mortality. Methods This study used data from 2946 NHANES (1999–2002) participants to analyze the relationship between weight-adjusted waist index (WWI) and sarcopenia (diagnosed using five different established criteria). Multivariable logistic regression, ROC analysis, Kaplan–Meier curves, and Cox regression were used to assess the association between WWI and sarcopenia and mortality. Results WWI was inversely correlated with walking speed, muscle strength, and muscle mass. It served as a significant predictor of sarcopenia, particularly in men, with an area under the ROC curve (AUC) of 0.86 for men according to FNIH criteria. Furthermore, a higher mortality rate from all causes was linked to a higher WWI. The mortality rate among patients with sarcopenia, as predicted by the WWI and FNIH criteria, was higher than that of patients diagnosed by a single criterion. Conclusions WWI proves to be a valuable tool in predicting sarcopenia and mortality risk, particularly when using the FNIH criteria. However, its performance varied significantly across different criteria and populations. Further research is needed to define the specific clinical contexts where WWI may be a useful supplementary tool. Level of Evidence Level III, evidence obtained from a cohort analytic study.